Analysis of Loss of Telomeric DNA During Replicative Aging of Human Cells and Examination of the Role of this Process in the Induction of Cell Senescence - Allsopp, Charles Richard (My University, 1995)
Telomeres are nucleoprotein complexes located at the ends of all eukaryotic chromosomes, and are essential for genetic stability and viability. Telomere length decreases during replicative aging of normal human diploid fibroblasts (HDF) in vitro. These observations imply that telomere length provides a mitotic clock for the replicative age of normal somatic cells, and that telomere shortening may cause cell senescence. To further examine these predictions, telomere length was analyzed (i) on vitro, in young HDFs as well as senescent and near-senescent HDFs and (ii) in vivo, in HDFs and candidate hematopoietic stem cells. Mean terminal restriction fragment (TRF) length decreased significantly at a rate of ~ 15 bp/year in HDFs. Also, mean TRF length decreased with increasing donor age in CD34⁺CD38^(lo) hematopoietic cells obtained from fetal donors and adult donors of ages 19 and 59 years. These observations confirm that telomere length decreases not just during aging in vitro but also during aging in vivo. They also, imply that stem cells have a finite lifespan.
The observations that telomere length is proportional to replicative capacity in cultured HDFs from normal and progeroid donors and that telomere length is shorter in HDFs at the periphery of radial outgrowths relative to HDFs at the center suggest that telomere length is a valuable marker for replicative potential.
Interclonal variability in telomere length was significantly less at senescence than at early passage for HDF clones established from the same strain, in support of the existence of a critical telomere length in senescent cells. Calculation of mean telomere length at senescence for these clones and one other HDF strain yielded an upper estimate of 2-3 kb for the critical telomere length. However, the detection frequency of individual telomeres by fluorescent in situ hybridization (FISH) varied from telomere to telomere in both young and senescent cells. Furthermore, in pre-crisis SW26 fibroblasts, the long arm of one copy of chromosome 9, which has a relatively short telomere, is frequently engaged in an end-to-end dicentric chromosome. Also, a significant distribution of TRF lengths exists at all PDLs. These observations indicate that the shortest telomere length at senescence, which best represents the critical telomere length, is probably considerably less than 2-3 kb.
These observations support a causal role of telomere shortening in cell senescence. This has important implications for future treatment of cancer and therapeutic prevention of cell senescence during aging.
Keywords: Biochemistry; Biochemistry